Precocious expression of Blimp1 in B cells causes autoimmune disease with increased self-reactive plasma cells - Bönelt, P; Wöhner, M; Minnich, M; Tagoh, H; Fischer, M; Jaritz, M; Kavirayani, A; Garimella, M; Karlsson, M; Busslinger, M (EMBO Press, 2018)
The transcription factor Blimp1 is not only an essential regulator of plasma cells, but also a risk factor for the development of autoimmune disease in humans. Here, we demonstrate in the mouse that the Prdm1 (Blimp1) gene was partially activated at the chromatin and transcription level in early B cell development, although mature Prdm1 mRNA did not accumulate due to posttranscriptional regulation. By analyzing a mouse model that facilitated ectopic Blimp1 protein expression throughout B lymphopoiesis, we could demonstrate that Blimp1 impaired B cell development by interfering with the B cell gene expression program, while leading to an increased abundance of plasma cells by promoting premature plasmablast differentiation of immature and mature B cells. With progressing age, these mice developed an autoimmune disease characterized by the presence of autoantibodies and glomerulonephritis. Hence, these data identified ectopic Blimp1 expression as a novel mechanism, through which Blimp1 can act as a risk factor in the development of autoimmune disease.